Cognitive Deficits and White Matter Alterations in Highly Trained Scuba Divers - Coco, Marinella; Buscemi, Andrea; Perciavalle, Valentina; Maci, Tiziana; Galvano, Gianluca; Scavone, Antonio M. F.; Perciavalle, Vincenzo; Di Corrado, Donatella (Frontiers in Psychology, 2019)
Nitrogen gas (N2), present in the normal atmospheric air, is a potential source of risk for scuba divers. It seems probable that myelin can represent, in hyperbaric conditions, a preferential site for the accumulation of N2 in CNS. The purpose of this study is to verify whether the practice of the scuba diving is capable to determine a damage of the brain white matter (WM) in a dose dependent manner and, consequently, possible deficiency of their cognitive abilities. For this purpose, 54 professional scuba divers (35 men and 19 women), with at least 2,000 dives in their careers, were studied. Possible alterations of brain WM were evaluated in terms of Fractional Anisotropy (FA) by using Diffusion Tensor Imaging, whereas possible cognitive impairments were verified by means of neuropsychological testing, by studying: 1) General mental capability 2) Executive functioning; 3) Visuospatial/visual construction; 4) Attention and orientation: 5) Selective attention capacity and processing speed ability; 6) Memory. The present results showed alteration of the WM in terms of changes in FA; these alterations, statistically significant but quantitatively quite modest, were mainly observed in the WM of the anterior part of the brain, whereas no differences were observed between left and right hemisphere. The alterations of the WM were associated with changes, also in this case statistically significant but quantitatively quite modest, of the cognitive functions, in particular of those dependent on the prefrontal cortex. The present study leads to the conclusion that repeated dives, even performed in compliance with the current decompression tables, can progressively lead in the CNS to the formation of micro-lesions in the myelin sheet capable of altering the functioning of the neuron.